PENGUATAN KELEMBAGAAN GABUNGAN KELOMPOK TANI (GAPOKTAN) DALAM PEMANFAATAN SUMBER DAYA LOKAL DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Sari, Iis Kurnia; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Combined farmer group (gapoktan) is a collection of several farmer groups that join and work together to improve economies of scale and business efficiency. The formation of a combination of farmer groups (gapoktan) is based on the concern of rubber farmers against the declining rubber prices and the marketing of rubber controlled by intermediate traders. With the area of rubber plantation in Gunung Toar subdistrict is quite wide and in general the livelihood of the community as a rubber farmer causes a variety of rubber prices. Because of the uniformity of rubber prices and seasonal changes and the lack of quality of human resources, organizational development is needed for the welfare of members who are members of a group of farmers (gapoktan). The theoretical concepts used are the techniques and approaches of agents of change in organizational development, proposed by Rivai and Mulyadi who say in the techniques and approaches of change agents in organizational development there are five kinds: sensitivity training, survey feedback, process consultation, team building, and intergroup development. The purpose of this study was to determine the strengthening of the Joint Group Agribusiness Institution (Gapoktan) in the Utilization of Local Resources In Gunung Toar Sub-district Kuantan Singingi Regency as well as the factors that influence it. This research uses qualitative method with descriptive data assessment. In collecting data of researcher using purposive sampling method and incidental sampling as information and data analysis. The results showed that the combination of farmer groups (gapoktan) in Gunung Toar sub-district in the utilization of local resources has not been able to improve the welfare of members and has not been able to answer the problem of the combined farmer groups (gapoktan). Factors that influence the environmental factors that groups and work culture is still less effective, the technology is still traditional and progress personnel and productivity that has not been reliable.Keywords : Organizational Development, Combined Farmer Groups, Local Resources